Structure and Metamorphism of Markam Gneiss Dome From the Eastern Tibetan Plateau and Its Implications for Crustal Thickening, Metamorphism, and Exhumation. (3rd January 2019) - Zhao, Z. B.; Du, J. X.; Liang, F. H.; Wu, C.; Liu, X. J.
Abstract: Gneiss domes developed in the eastern Songpan‐Ganzi Flysch (SGF) belt, located in the hinterland of the Longmen Shan Thrust belt of the eastern Tibetan Plateau. These domes have similar pressure‐temperature (denoted as P‐T below) paths and formed during Late Triassic‐Early Jurassic. One of them, the Markam Gneiss Dome (MGD), is cored by granite and is mantled by a metaturbidite aureole. Our structural observations show top‐to‐the‐south shearing that transposed an upright S1 foliation into a flat‐lying NW‐SE striking S2 composite foliation in the Triassic metaturbidites. Thin sections reveal that the metamorphic index minerals biotite, garnet, and staurolite grew prior to the transposition into S2, whereas kyanite and sillimanite crystallized syn‐S2 development. P‐T pseudosections for the metaturbidites indicate a temperature peak of approximately 618–632 °C and a pressure peak of approximately 6–8 kbar. The highest P‐T condition was immediately followed by isothermal decompression, which is represented by the sillimanite overgrowing andalusite and biotite. Granite was emplaced at ~10‐ to 15‐km depth, during isothermal decompression. Zircon U‐Pb geochronology of metaturbidites, granite, and pegmatite of the MGD indicates that (1) the metaturbidites are younger than 240 Ma, (2) the granite was mainly sourced from the metaturbidites, and (3) deformation leading to the transposition of S1 into S2 mainly occurred ca. 215–170 Ma. Our new P‐T‐D‐t results from the MGD confirm those of other gneiss domes in the SGF and indicate Late Triassic‐Early Jurassic crustal shortening and thickening that probably reflects coeval low‐viscosity crustal flow of the SGF. Key Points: Metaturbidites record S1 foliation transposed to composite S2 and highest P‐T conditions at 618‐632 degrees Celsius and 6‐8 kbar in the Markam Gneiss Dome Granite emplaced after initial exhumation of the metaturbidites and led to isothermal decompression metamorphism Developing gneiss domes indicate Late Triassic crustal thickening in the eastern Tibetan Plateau